(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article describes the ways of expressing the assessment in the axiological picture of the world of Boris Pilnyak – one of the most rationalist prose writers of the 20-30s of the XX century (V. Hoffman). During the study, it was found that the evaluation function is one of the most important in the language in general and in artistic speech in particular, because it expresses the speaker’s attitude to any fact, event, phenomena, object. It helps to express the author’s position in the texts and to reflect the author’s value system. It was revealed that the use of various methods of expressing assessment (evaluative vocabulary, evaluative word-formation means, evaluative grammatical means, visual expressive means) is typical for B. Pilnyak: appraisal permeates all levels of his artistic speech; estimate verbal images are created; through the categories of assessment and appraisal, the author’s worldview and worldview are expressed, reflected in his creative method and making up the core of his axiological picture of the world. Ontain an assessment and titles of B. Pilnyak’s works. Most of the titles, being a way of expressing the author’s modality, became allegorical images, images-symbols, and the author’s interpretation of the text. There are also melioratives in the writer’s texts that Express the speaker’s positive attitude to reality, to the person and his actions. The Russian language’s word-forming resources, which the writer uses skillfully, also contribute to the creation of evaluation in the text. Often emotional and expressive evaluation is expressed by means of diminutives.